Historia Katedry Prawa o Wykroczeniach, Karnego Skarbowego i Gospodarczego - Sawicki, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The Department of Petty Offences Law, Fiscal Criminal Law and Criminal Economic Law was established in 1997; however, it received its current name in 2015. Professor Marek Bojarski has been the Chair since its establishment. The Department carries out scientific research on issues regarding substantive and procedural criminal, criminal fiscal law and petty offence law. The Department of Petty Offences Law, Fiscal Criminal Law and Criminal Economic Law conducts numerous academic courses such as the Academic Course on Petty Offence law, the Academic Course on Fiscal Penal Law, the Academic Course on the Protection of Trading, the Academic Course on Legal Regulations for Uniformed Services. The academic staff of the Department also run extra-curriculum academic courses regarding, for example, Tax Offences, Juvenile Liability for Crimes and Offences, Road Traffic Offences. The research and teaching activity of the Department is reflected both in its academic publications and active participation in national and international scientific conferences. Professor Marek Bojarski graduated the University of Wrocław, where he also obtained his Ph.D. degree. He became Professor in 1992 in Wrocław. He has held numerous university positions: Vice-Director, Director, Dean, Vice-Dean, Vice-Rector, and has been the Rector of the University of Wrocław since 2008 and is currently in his second term in office. Professor Marek Bojarski has been a visiting professor to many universities worldwide, e.g. Boston University, American University in Washington, Leiden University, Leuven Catholic University, Branderburg University of Technology Cottbus-Senftenberg. He is also a member of various societies, e.g. Association Internationale De Droit Pénal, Scientific Society for Penal Law, Society for Environmental Protection; and he sits on boards, such as: Legislative Board, Advisory Board of the Central Anti-Corruption Bureau. ProfessorMarek Bojarski is the Chair of Revision Committee for the Conference of Rectors of Academic Schools in Poland and the Chair of the Conference of Rectors of Silesian Universities. He is an Honorary Professor at the University of San Martin de Porres in Lima, the Catholic University of Santa María in Arequipa and the Centre of Higher Education in Pachuca; and he holds the title of Doctor Honoris Causa awarded by the following universities: the Tomsk State Pedagogical University, the Ivan Franko National University of Lviv, the Mykolas Romeris University in Vilnus, the Lithuanian Educological University in Vilnius. Professor Marek Bojarski is the author of over 200 academic publications.Associate Professor Janusz Sawicki has worked at the Department of Petty Offences Law, Fiscal Criminal Law and Criminal Economic Law since its establishment. He received Ph.D. degree at the University of Wrocław. He became Associate Professor in 2012. His main interests are related with fiscal penal law, criminal law and petty offences law. He is responsible for supervising part-time Ph.D. students. He has held many university positions, for example Disciplinary Proceedings Representative for Students or Coordinator of Enrolment Committee. He decides on the Appeal Disciplinary Committee for Academic Staff at the General Council for Science and Higher Education. He is a member of Polish Platform for Homeland Security. Associate Professor Janusz Sawicki is the author of almost 50 academic publications.
Keywords: The Department of Petty Offences Law, Fiscal Criminal Law and Criminal Economic Law; Faculty of Law, Administration and Economics; University of Wrocław; history